Linkage Analysis of Physics Concepts in the Bom-bom Car Game at Lamongan Marine Tourism - Sindy Regita Cahyani; Tsung-Hui Cheng (Studies in Philosophy of Science and Education, 2022)
The implementation of Physics learning must be contextual where during the learning process it is made by exploring the knowledge possessed and associated with its application in real life in the community environment of students. In learning physics students are required to be able to understand concepts, theories, principles, laws, and models and it is expected that through scientific processes they are able to have skills in developing knowledge during the learning process carried out. However, there are still many students who do not understand the linkages of contextual learning and only focus on understanding concepts according to the specified textbooks. The purpose of this research is to increase students' learning motivation by analyzing the relationship between physics concepts and the bom bom car game at Wisata Bahari Lamongan. The research method used is descriptive-qualitative. Through observation, interviews, literature review and documentation is done as a data collection technique. It can be concluded that the bom–bom car game at Lamongan Marine Tourism has a connection with the concept of physics, namely the concept of Newton's Third Law, momentum, impulse, and collision.